Patient web portals, disease management, and primary prevention - Coughlin SS; Prochaska JJ; Williams LB; Besenyi GM; Heboyan V; Goggans DS; Yoo W; De Leo G (Dove Medical Press, 2017)
Steven S Coughlin,1 Judith J Prochaska,2 Lovoria B Williams,3 Gina M Besenyi,1 Vahé Heboyan,1 D Stephen Goggans,4 Wonsuk Yoo,5 Gianluca De Leo1 1Department of Clinical and Digital Health Sciences, College of Allied Health Sciences, Augusta University, Augusta, GA, 2Department of Medicine, Stanford Prevention Research Center, Stanford University, Stanford, CA, 3Department of Biobehavioral Nursing, College of Nursing, Augusta University, 4Department of Public Health, East Central Health District, 5Institute of Public and Preventive Health, Augusta University, Augusta, GA, USA Background: Efforts aimed at health care reform and continued advances in information technologies have prompted interest among providers and researchers in patient web portals. Patient web portals are password-protected online websites that offer the patients 24-hour access to personal health information from anywhere with an Internet connection.Methods: This article, which is based upon bibliographic searches in PubMed, reviews important developments in web portals for primary and secondary disease prevention, including patient web portals tethered to electronic medical records, disease-specific portals, health disparities, and health-related community web portals.Results: Although findings have not been uniformly positive, several studies of the effectiveness of health care system patient portals in chronic disease management have shown promising results with regard to patient outcomes. Patient web portals have also shown promising results in increasing adherence with screening recommendations. Racial and ethnic minorities, younger persons, and patients who are less educated or have lower health literacy have been found to be less likely to use patient portals.Conclusion: Additional studies are needed of the utility and effectiveness of different elements of web portals for different patient populations. This should include additional diseases and health topics such as smoking cessation and weight management. Keywords: chronic diseases, diabetes, electronic health record, health disparities, hypertension, health information technology, immunization, patient web portals, screening